Tradition and Experience: The Functional Theology of a Congregation at Worship (Hillcrest Mennonite Church) - Martin, Maurice (My University, 2001)
The thesis that this dissertation seeks to demonstrate is that the functional theology of a congregation at worship is shaped both by the received theological tradition in which it stands, and by primary theology as experienced and reported by the worshippers. The underlying assumption is that theology and worship are intrinsically linked; each time people worship they "do theology." This is primary theology, while secondary theology consists of reflection on this first-order experience. The Trinity is a "given" of the received faith in Christian worship.With this assertion as a starting point, the dissertation explores the implications of trinitarian language and thought for worship, beginning with the secondary theology of traditional orthodoxy, then proceeding to the primary theology of worship as experienced and described by those who worship at Hillcrest Mennonite Church. The dissertation takes a phenomenological approach: using interviews and a questionnaire, congregants were invited to describe their own experiences of worship, both in terms of general Christian orthodoxy and of Anabaptist theology. Hillcrest stands within the Anabaptist tradition, which shapes their theology and experience of worship. The dissertation describes Anabaptist history, theology, practice and worship, from which Mennonite theology and worship is derived. Such a description of the essential characteristics of Anabaptist-Mennonite worship determined a series of questions for the survey project, designed to measure the participants' affinity with Anabaptist indicators. Templates measuring personal piety, degree of communalism, ethics, and the relation to daily life were also used. The purpose of the project was to discover people's experience (primary theology) of worship. The desired outcome is to ensure that people at Hillcrest are nurtured by a worship which is both relevant to their personal experience, and authentically faithful to the tradition in which they stand.